2023
DOI: 10.3390/agronomy13051207
|View full text |Cite
|
Sign up to set email alerts
|

Complex Cd–Pb Multigenerational Exposure Improves the Growth and Food Utilization of the Cutworm Spodoptera litura

Abstract: Concurrent exposure to cadmium (Cd) and lead (Pb) is prevalent in the environment, but information on the long-term impacts of complex Cd–Pb exposure on herbivorous insects, especially at low doses, is scant. We studied the effects of complex Cd–Pb exposure (4.06 mg/kg Cd and 12.5 mg/kg Pb) on the growth and food utilization of the herbivorous insect Spodoptera litura for 10 continuous generations. Cd or Pb ingestion, excretion and accumulation by insect at the different developmental stages was determined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Superoxide dismutase (SOD) is a ubiquitous enzyme family that catalyzes the dismutation of superoxide anions effectively. A study by Adesina [ 60 ] reported that SOD activity in insects treated with herbal insecticide formulations increased with the concentration and exposure time. Increased concentrations of active components in all treated samples stimulated SOD production, resulting in higher dismutation of superoxide anions (O 2− ).…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase (SOD) is a ubiquitous enzyme family that catalyzes the dismutation of superoxide anions effectively. A study by Adesina [ 60 ] reported that SOD activity in insects treated with herbal insecticide formulations increased with the concentration and exposure time. Increased concentrations of active components in all treated samples stimulated SOD production, resulting in higher dismutation of superoxide anions (O 2− ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this study, the cadmium contents in sweet potato chips and weevils were not determined for all treatments, which need to be further clarified in the subsequent studies on Cd accumulation. In addition to appetite, heavy metals have other toxic effects on insects; in severe cases, they have adverse effects on the growth index, development duration, and mortality rate [ 15 , 46 , 47 ]. Exposure of insects to Cd 2+ can delay development [ 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the impacts of heavy metal exposure on herbivorous insects is particularly important for assessing eco-toxicological risk in food chains [ 46 ]. In addition, the development of insect heavy metal tolerance has probably led to the increase in their tolerance to pesticides [ 7 , 43 ], which may reduce the efficiency of pest chemical control and bring new challenges to pest control in the farmland with heavy metal pollution [ 46 ]. In this study, weevil resistance to spinetoram increased after exposure to a low level of Cd 2+ , but the sensitivity to B. bassiana was not affected by Cd contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation